2010
DOI: 10.1002/ana.21937
|View full text |Cite
|
Sign up to set email alerts
|

L‐type calcium channel blockers and Parkinson disease in Denmark

Abstract: Objective-Investigate L-type calcium channel blockers of the dihydropyridine class for association with Parkinson's disease because these drugs traverse the blood brain barrier, are potentially neuroprotective, and have previously been evaluated for impact on PD risk.Methods-We identified 1,931 patients with a first time diagnosis for PD between 2001 and 2006 as reported in the Danish national hospital/outpatient database and density matched them by birth year and sex to 9,651 controls from the population regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(208 citation statements)
references
References 23 publications
(29 reference statements)
6
201
0
1
Order By: Relevance
“…Ruthenium red has recently been shown to improve mitochondrial ATP levels and membrane potentials in neurons expressing mutant ␣-synuclein and/or PINK-1 associated with Parkinson disease (22). Furthermore, L-type calcium blockers have been suggested to reduce the chance of developing Parkinson disease (23). More recently, the selective TRPV4 channel blocker, HC-067047, has been shown to improve bladder function in experimentally induced cystitis in rodents without any major side side effects (24).…”
Section: Discussionmentioning
confidence: 99%
“…Ruthenium red has recently been shown to improve mitochondrial ATP levels and membrane potentials in neurons expressing mutant ␣-synuclein and/or PINK-1 associated with Parkinson disease (22). Furthermore, L-type calcium blockers have been suggested to reduce the chance of developing Parkinson disease (23). More recently, the selective TRPV4 channel blocker, HC-067047, has been shown to improve bladder function in experimentally induced cystitis in rodents without any major side side effects (24).…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study of hypertensive patients found a significant reduction in the observed risk of PD with CCA use, but not with medications that reduce blood pressure in other ways (9). More recently, a large Danish data set has been examined (100 …”
Section: Surmeier Et Almentioning
confidence: 99%
“…They have been developed as cardiovascular drugs, blocking L-type (Ca V 1) calcium channels. Amlodipine blocks Ca V 1.2 with IC 50 =100 nM and Ca V 2.1 with IC 50 =10 M. Many drugs from the group of dihydropyridines crossing blood-brain barrier, including nifedipine and nimodipine (and excluding amlodipine), proved efficacy in preventing Parkinson's disease in over 25% of patients [128]. However, in an animal study, nifedipine lowered anticonvulsant activity of topiramate in mice (it doubled its ED 50 ).…”
Section: Nifedipinementioning
confidence: 99%